PSYCHOLOGICAL AND PEDAGOGICAL IMPORTANCE OF PREPARING GIRLS FOR FAMILY LIFE (Scientific journal of the Fergana State University, 2024)
In this article, we present and analyze from a pedagogical point of view the psychological and pedagogical significance of preparing girls for family life, various methods that allow girls to realize the value and sanctity of the family from childhood.